2005
DOI: 10.1080/13645700500272413
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental aspects of learning minimally invasive surgical skills

Abstract: With the introduction of minimally invasive surgery (MIS) the necessity to develop training methods to learn skills outside the operating room (OR) became clear. Several training simulators have become commercially available. However, fundamental research into the requirements for effective and efficient training in MIS is still lacking. Yet in the literature several learning models have been described that may be used when designing the structure of a training program. While learning skills, three stages can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 26 publications
(23 reference statements)
0
53
0
1
Order By: Relevance
“…It has been demonstrated that neither one performance measure ñor efficiency metrics alone adequately measure competence, since competence is multi-factorial in nature, with knowledge, judgment, behavior, and technical abilities each playing a major role [60,61]. Therefore, various performance measures that are essential for surgical competence need to be taken into account.…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%
“…It has been demonstrated that neither one performance measure ñor efficiency metrics alone adequately measure competence, since competence is multi-factorial in nature, with knowledge, judgment, behavior, and technical abilities each playing a major role [60,61]. Therefore, various performance measures that are essential for surgical competence need to be taken into account.…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%
“…Training results and expert feedback should be available, especially in the beginning, in order to avoid misapprehension (47). The exercises should include partial tasks, supportive feedback and several goals to strive for (46). Expertise in complex visuo-motor skills can not be reached without repetition and deliberate practice (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Learners should be enabled to follow their own progress and receive adequate feedback and evaluation (46). A simulator can be connected to an interactive social context in which facilitation and peer support promotes learning.…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop an advanced and comprehensive objective assessment, a three-dimensional evaluation of trainees is necessary to obtain the right balance of attributes: A good knowledge base, surgical judgement and technical skills (59). Traditional evaluation methods for minimally invasive surgery based on subjective criteria suggest that an objective and automatic assessment method of surgical skills should be standardized to cope with mentors' and trainees' tight schedules, saving when possible the extra cost of having an experienced surgeon during the entire evaluation process, and as a means towards proficiencybased curricula for training in laparoscopic surgery and its certification.…”
Section: Discussionmentioning
confidence: 99%